A variação dos verbos ter e haver existenciais em revistas da Turma da Mônica: uma análise em tempo real de 1970 até 2010 - Machado, Amanda Henriques (2025)
Based in the Theory of Linguistic Variation and Change (WEINREICH; LABOV; HERZOG, 2006 [1968]), this dissertation examines the variation between the existential verbs ter and haver through a real-time study designed to describe and interpret an ongoing linguistic change in Brazilian Portuguese. Previous research (AVELAR, 2006; CALLOU; AVELAR, 2000, 2012; DUARTE, 2003; DUTRA, 2000; SIBALDO; CORREIA, 2014; VITÓRIO, 2008, 2010, 2013) has consistently shown the progressive expansion of ter to the detriment of haver in both oral and written modalities. Drawing on a corpus of 178 issues of Turma da Mônica magazines published between the 1970s and 2010s, this study investigates how the alternation between ter and haver manifests in existential constructions, considering linguistic, semantic, and extralinguistic factors and tracking the behavior of the variants over five decades. The choice of comic books as the object of analysis is justified by their multimodal textual-discursive nature, combining verbal and visual language to construct a planned representation of orality. In Turma da Mônica, this representation is anchored in characters of diverse social profiles, age groups, and sociocultural settings, which makes the corpus particularly suitable for Variationist analysis. As a major editorial phenomenon and a cultural and linguistic heritage, the series also reflects social concerns, debates on linguistic prejudice, and the legitimization of different varieties of Portuguese, playing a central role in readers’ linguistic socialization. From a methodological point of view, the study adopts a quantitative and qualitative approach, with statistical treatment carried out using the R platform in the RStudio interface and the GoldVarb X program. The dependent variable ter and haver is analyzed as a function of independent linguistic variables (tense and mood, type of construction, position of the noun phrase and presence of elements to the left of the verb), semantic variables (nature of the internal argument) and extralinguistic variables (decade and year of publication, character, life stage and locality). The results show a continuous and significant advance of the innovative variant ter over the five decades analyzed. In 1970, ter appears with a frequency of 28.70%, but in the following decade it already jumps to 75.59%. This growth continues in the subsequent decades, reaching 90.09% in 2010. In parallel, haver is progressively reduced and becomes concentrated in contexts determined by verbal tense and in characters whose speech is associated with more conservative traits. The linguistic, semantic and social analyses confirm that this change is not abrupt, but gradual, multifactorial and socially motivated. It is concluded that the Turma da Mônica magazines record and disseminate the consolidation of ter as the predominant existential verb, in addition to demonstrating the relevance of comic books as a productive source for the investigation of phenomena of linguistic variation and change.